Taxonomic notes on the crab spider genus Tobias Simon, 1895 (Araneae, Thomisidae, Stephanopinae) - Machado, Miguel; Teixeira, Renato Augusto; Lise, Arno Antonio (Zootaxa, 2015)
The males of Tobias caudatus Mello-Leitão, 1929 and Tobias pustulosus Simon, 1929 are described for the first time, females are redescribed and both sexes are illustrated. New distribution records are presented for both species. Tobias monstruosus Mello-Leitão, 1929 is considered a junior synonym of T. pustulosus. The types of Tobias albovittatus Caporiacco, 1954, and Tobias gradiens Mello-Leitão, 1929 are lost, and Tobias albicans Mello-Leitão, 1929 and Tobias corticatus Mello-Leitão, 1917 are known only from poorly preserved specimens, thus they all are considered nomina dubia.